The relationship between psychological resilience and older adults' self-reported driving comfort, abilities, and restrictions. (June 2020) - St. Louis, Renée M.; Koppel, Sjaan; Molnar, Lisa J.; Di Stefano, Marilyn; Darzins, Peteris; Bédard, Michel; Mullen, Nadia; Myers, Anita; Marshall, Shawn; Charlton, Judith L.
Abstract: Objective: This exploratory study examined the concept of psychological resilience and self-reported measures of driving comfort, abilities, and self-regulatory driving behavior in adults aged 75 years and older (Male: 69.9%; Mean age = 81.6 years, SD = 3.3, Range = 76.0–90.0). As resilience is associated with adaptive coping skills, it was anticipated that older drivers with higher resilience scores would be more likely to exhibit self-regulatory driving behavior. Method: Participants from the Ozcandrive older driver cohort study (Melbourne, Australia) completed: a demographic questionnaire; a battery of functional/health assessments; driving comfort, perceived abilities and self-regulatory scales; and a resilience scale. Data for a subset of 183 participants were analyzed. Results: Hierarchical regression analyses using age, sex, driving exposure, and resilience showed that adding resilience into the models resulted in statistically significant increases in the amount of variance explained, however, the resulting total R-squared values remained modest (i.e. R 2 between 0.074 and 0.305). After combining all variables into each model, resilience remained significant in all models except situational driving avoidance. Findings for females support the hypothesis that those with higher resilience report more self-regulatory driving behavior, with contrasting findings for males. Discussion: The current findings add to the literature on factors influencing later-life driving decisions and provide more information for extending safe mobility for older adults. The study highlights a promising new domain of research to understand how older adults navigate the process of aging and driving and can provide stakeholders with more information to best prepare for the transportation and mobility issues that lie ahead. Highlights: First study to investigate resilience within the context of health and driving. Women reported higher levels of resilience and self-regulatory driving behavior. Further exploration of changes in resilience, health, and driving is warranted.